2022
DOI: 10.1039/d2py00150k
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylpyridine)-containing block copolymers for smart, multicompartment particles

Abstract: Multicompartment particles generated by the self-assembly of block copolymers (BCPs) have received considerable attention due to their unique morphologies and functionalities. A class of important building blocks for multicomponent particles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 185 publications
0
22
0
Order By: Relevance
“…One promising approach to tune the interfacial and structural properties of BCP-containing emulsions is the incorporation of organic/inorganic additives that interact with one of the BCP blocks. In particular, BCPs containing pyridinyl-based monomer units have been widely used to integrate organic/inorganic guest materials via non-covalent bindings including ionic interactions and hydrogen bonding. For example, hydrolysis of Fe­(III) ions co-assembled with polystyrene- block -poly­(4-vinylpyridine) (PS- b -P4VP) induced the protonation of P4VP units, which triggered the splitting of emulsion droplets into nanosized micelles . In addition, alkyl halide additives have been reported to induce an interesting shape transition of ellipsoidal polystyrene- block -poly­(2-vinylpyridine) (PS- b -P2VP) BCP particles into larva and disassembled spheres .…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach to tune the interfacial and structural properties of BCP-containing emulsions is the incorporation of organic/inorganic additives that interact with one of the BCP blocks. In particular, BCPs containing pyridinyl-based monomer units have been widely used to integrate organic/inorganic guest materials via non-covalent bindings including ionic interactions and hydrogen bonding. For example, hydrolysis of Fe­(III) ions co-assembled with polystyrene- block -poly­(4-vinylpyridine) (PS- b -P4VP) induced the protonation of P4VP units, which triggered the splitting of emulsion droplets into nanosized micelles . In addition, alkyl halide additives have been reported to induce an interesting shape transition of ellipsoidal polystyrene- block -poly­(2-vinylpyridine) (PS- b -P2VP) BCP particles into larva and disassembled spheres .…”
Section: Introductionmentioning
confidence: 99%
“…Block copolymers (BCPs) made up of distinct different segments linked by covalent bonds can spontaneously self-assemble into various nanosized micelles or particles, which have great potential in catalysis, devices, diagnostics, and drug delivery. Recently, it has been reported that BCPs can assemble into some unique nanostructured particles when they are confined within organic emulsion droplets. With the gradual evaporation of emulsion solvent, BCPs are aggregated together and phase separated, thus forming well-ordered polymeric nanoparticles. This strategy is called emulsion solvent evaporation-induced self-assembly or confined self-assembly within emulsion droplets. Compared to the self-assembly of BCPs in solution or the bulk state, there is a template effect and structural frustration imposed by the spherically confined geometry as the self-assembly of BCPs occurs inside the emulsion droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Besides generating BCP particles with different shapes or structures during the self-assembly process, it is more attractive to fabricate the shape-switchable BCP particles that can change their morphology and internal structure triggered by external stimuli. Stimuli-responsive surfactants have been introduced into the emulsion confined self-assembly of BCPs to regulate the internal structure and the morphologies of the resulting BCP particles via external stimuli. , For instance, Kim and co-workers developed pH-responsive shape-switchable particles by introducing pH-responsive surfactants into the self-assembly of polystyrene- b -poly­(4-vinylpyridine) (PS- b -P4VP) within the emulsions, which exhibited the shape reversibility over continuous cycles of pH variations . In our previous work, we employed a light-active surfactant to realize reversibly light-responsive morphological transformation between onion-shaped particles with a PS outermost layer and the inverse onion-like particles with a P4VP outermost layer .…”
Section: Introductionmentioning
confidence: 99%